2022
DOI: 10.3389/fphys.2022.984760
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 mediates high glucose-induced mitochondrial fission through activation of CDK5 in cultured human podocytes

Abstract: Mitochondrial abnormalities contribute to the development of diabetic nephropathy (DN). However, the precise mechanisms of mitochondrial dysfunction in DN remain unclear. Transient receptor potential canonical channel-6 (TRPC6), a non-selective cation channel permeable to Ca2+, has been shown to regulate mitochondrial dynamics. This study was therefore aimed to explore the regulatory role and mechanisms of TRPC6 in high glucose (HG)-induced mitochondrial dysfunction in podocytes. Here we found that TRPC6 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In kidney, Cdk5 regulates the differentiation, proliferation, and morphology of podocytes and plays an important role in maintaining the normal structure and function of podocytes 12 . In diabetes, hyperglycemia, TGF‐β1, and endoplasmic reticulum stress could overactivate Cdk5 and lead to podocyte injury and apoptosis 13–15 . Although many studies have shown that hyperactivated Cdk5 is associated with the podocyte injury in DKD, the exact mechanism still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In kidney, Cdk5 regulates the differentiation, proliferation, and morphology of podocytes and plays an important role in maintaining the normal structure and function of podocytes 12 . In diabetes, hyperglycemia, TGF‐β1, and endoplasmic reticulum stress could overactivate Cdk5 and lead to podocyte injury and apoptosis 13–15 . Although many studies have shown that hyperactivated Cdk5 is associated with the podocyte injury in DKD, the exact mechanism still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…12 In diabetes, hyperglycemia, TGF-β1, and endoplasmic reticulum stress could overactivate Cdk5 and lead to podocyte injury and apoptosis. [13][14][15] Although many studies have shown that hyperactivated Cdk5 is associated with the podocyte injury in DKD, the exact mechanism still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%